UPAYA GURU PAI DALAM MENINGKATKAN KECERDASAN INTERPERSONAL SISWA (STUDI KUALITATIF NATURALISTIK DI SMPN 02 CIBITUNG) - Khadijah -; Abdul Khoir HS (Turats, 2020)
This study describes the efforts of Islamic Religious Education teachers in improving students'interpersonal intelligence and analyzes the supporting and inhibiting factors in improving students'interpersonal intelligence at SMPN 02 Cibitung. The data analysis technique in this study was carriedout by data reduction, namely emphasizing, sharpening, and removing unnecessary things from thedata obtained and then presenting the data by describing the data that had been sorted systematicallyand finally drawing conclusions from the results of the study. The results of the study explained that theteacher's efforts to improve students' interpersonal intelligence were through practicing the 3S (smile,greeting, and greeting) and applying the 4 magic words (sorry, thank you, excuse me and pleasehelp) as a socializing attitude. Supporting factors in improving students' interpersonal intelligenceare found in the assessment of attitudes, rules, and school ethics. Then the inhibiting factor is the lowinterest of students in Islamic religious lessons.